Implementation of Open Source Integrated Library System in Academic Libraries of Pakistan: A Proposed Framework - Chandio, Abida Kanwal; Chandio, Shahmurad; Nizan, Noor Hasrul (2017)
An interrelated group of computer programmes that automates multiple library operations called integrated library system. In Pakistan, the condition concerning library software cannot be associated with the that in developed countries, it’s not satisfactory due to absence of software systems used for making modern libraries, less budget, multilingual nature of library’s collection, software privacy and absence of provision from regional vendors are the key barriers in the impressive implementations of integrated library system. The Objective of this paper is to propose an open source integrated library system implementation framework to boost the academic library standard, provide capability to resource sharing and library users can able to access the information material at any time regardless of their geographical location. This research is grounded on comprehensive literature review that includes the journal articles, conference proceedings, thesis, books and libraries websites by the help of literature review the suggestion and the recommendation will give to the library professionals about criteria of selecting the open source-ILS and how to overcome problems and challenges faced by implementation of open source-ILS. Meanwhile this study will also focus on prevailing standards in developed world for Management of libraries and providing specific directions for upbringing of academic libraries in Pakistan.